2021
DOI: 10.3233/sji-200711
|View full text |Cite
|
Sign up to set email alerts
|

Updating the paradigm of official statistics: New quality criteria for integrating new data and methods in official statistics

Abstract: This paper aims to elicit a discussion of the existence of a paradigm shift in official statistics through the emergence of new (unstructured) data sources and methods that may not adhere to established and existing statistical practices and quality frameworks. The paper discusses strengths and weaknesses of several data sources. Furthermore, it discusses methodological, technical and cultural barriers in dealing with new data and methods in data science; cultural as in the culture that reigns in an area of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Task Team suggested a Framework for the Quality of Big Data [13] which uses a hierarchical structure composed of the three hyper-dimensions: source, metadata, and data. More recently, De Broe et al have discussed quality criteria for integrating new data and methods in official statistics [14] and concluded that the European Statistical System quality principles as laid down in the European Statistics Code of Practice and hence also in the UN-NQAF, do not need to be adapted to the emergence of new data sources. De Broe et al argue that new quality aspects associated with big data sources can be integrated into existing quality frameworks at the level below the respective quality principles.…”
Section: Approaches To Assess the Quality Of Source Datamentioning
confidence: 99%
“…Task Team suggested a Framework for the Quality of Big Data [13] which uses a hierarchical structure composed of the three hyper-dimensions: source, metadata, and data. More recently, De Broe et al have discussed quality criteria for integrating new data and methods in official statistics [14] and concluded that the European Statistical System quality principles as laid down in the European Statistics Code of Practice and hence also in the UN-NQAF, do not need to be adapted to the emergence of new data sources. De Broe et al argue that new quality aspects associated with big data sources can be integrated into existing quality frameworks at the level below the respective quality principles.…”
Section: Approaches To Assess the Quality Of Source Datamentioning
confidence: 99%
“…The presence of Big Data is expected to have a major impact on institutions that produce, process and analyze data and information (De Broe et al, 2021). Band the Statistics Center or often abbreviated as BPS is one of these organizations.…”
Section: The Impact Of the Imposition Of Big Data Access Fees And The...mentioning
confidence: 99%
“…However, many barriers have been met that made implementation rather challenging which range from methodological to technical and cultural challenges. An overview of these can be found in [3]. In effect, Statistics Netherlands was not able to implement these new outputs until now except for the two already existing statistics (traffic intensity using traffic loop data and Consumer Price Index using the scanner data).…”
Section: The Innovation Processmentioning
confidence: 99%